Why publish in a scientific journal? - Arroyo-Hernández, Hugo (2019)
After calling your attention, I hope that you, dear reader, have one or more answers to the question. If not, let me provide you with some answers. First it is necessary to recognize the importance of doing scientific research; however, its discussion always leads us to the need for the development and generation of new knowledge. A conclusion that we also hear within the university environment. Doing research is necessary and important for the University